Professional Zakat in Modern Society Life: Provisions Regarding Intellectual Property Objects, Nisab, and Zakat Level - Shabarullah Shabarullah; Fitria Andriani; Muhammad Sufyan Naim bin Shahrinizam (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2021)
Abstract: In the modern era, scholars have determined some of wealth that must be issued zakat beyond what has been stipulated in the text of the Al-Qur'an and as-Sunnah, and one of them is intellectual property. This article examines the opinions and arguments of the scholars regarding the inclusion of intellectual property rights as objects of zakat and both the nisab and zakat levels. This article is based on library data, both primary and secondary. Using a normative and historical approach and by utilizing modern zakat theory, this article concludes that intellectual property is part of wealth, which has both, benefits and economic value. Based on this fact, intellectual property is part of the object of zakat, namely the object of profession zakat. This is based on the general meaning of lafadz infaq in QS. al-Baqarah [2]: verse 267; the generality of the meaning of